Evaluation of the Application of Electronic Medical Record Based on the Perspective of the Inpatient User Toto Kabila Regional General Hospital Stay - Nurmita Hasan; Herlina Jusuf; Moh. Rivai Nakoe (Universitas Muhammadiyah Palu, 2025)
The application of Electronic Medical Record (EMR) as a digital technology in healthcare that is used to record and store patient handling data, has become a major need in the transformation of healthcare services in Indonesia. However, the success of its implementation is largely determined by user acceptance. This study aims to identify the application of EMR from the perspective of users in the inpatient room of the Toto Kabila Regional General Hospital as seen from the factors of work expectation, business expectations, social influence and facility conditions. This study used a quantitative approach of a descriptive method, with a population of 150 nurses and a sample of 109 inpatient nurses and data collection through questionnaires. Based on the results of the study, it was found that in the work expectations 32.11% of respondents rated it as good, 67.89% adequate; business expectations of 26.61% were good, 73.39% adequate; social influence 19.27% was good, 75.23% was adequate and 5.50% was lacking; facility conditions were 28.44% good, 69.72% were adequate and 1.83% were poor. Overall, the implementation of EMR at Toto Kabila Hospital was considered good by 30.28% of respondents, and adequate by 69.72%. It is suggested that the implementation of EMR in the inpatient Toto Kabila Hospital can run optimally, improvements are needed in the form of periodic system evaluation, development of EMR features, strengthening team collaboration, improving technology infrastructure, and supporting a responsive IT team.